The Influence of Science Comics Learning Media and Problem-Based Learning Methods on the Effectiveness of Support Solution Learning for Students of SMAN 1 Toraja Utara - Sulpa Dewi Rantetampang; Bernadetha Nadeak; Mesta Limbong (International Journal of Educational Management and Innovation, 2023)
Education is one of the spearheads of a country's success. In education, the teacher is the spearhead; for this reason, the teacher must continue to improve himself to innovate and be creative in presenting the material being taught so that learning objectives can be adequately achieved. One is in chemistry learning, which must motivate students to continue developing critical thinking skills. For this reason, through this thesis, the writer will examine "The Influence of Science Comic Learning Media with MethodsProblem Based Learning on the Effectiveness of Buffer Solution Learning for SMAN 1 Toraja Utara students. This type of research is correlational and aims to determine the effect of Science Comics and Method media Learning as the independent variable on the effectiveness of learning as the dependent variable. The population of this study were students in class XI of the Mathematics and Natural Sciences Department of SMAN 1 Toraja Utara for the academic year 2022/2023, which consisted of 3 classes with a total of 96 students. The sample was taken randomly with 77 students using the Solvin formula N = n/N (d)2 + 1.  The effect of comic and media methods problem-based learning on the effectiveness of learning using a questionnaire from student observations on teacher teaching activities. The data obtained were analyzed based on descriptive analysis.